Methodology of recreation in the structure of educational space. - Zaytzev V.P; Iermakov S.S; Hagner-Derengowska Magdalena (Kharkov National Pedagogical University, 2011)
The article deals with the methodological aspects of health, healthy lifestyle and recreation, touching students in higher educational establishments. The historical moments of recreation and concept definition of recreation measures are presented. Certain descriptions of kinds and functions of recreation are given, and also recreation system, recreation districting, placing and correlation of objects of active rest. In the leadthrough of recreation measures occupies the desire of students and high professional level of doctors as no less important factor, occupation therapist, instructors, methodists of medical physical culture and cultural and educational workers. Presented problems were the purpose of researches and supervisions of scientists, teachers and doctors from Ukraine and Poland.